Efektivitas Pembelajaran Berbasis Masalah dengan Pendekatan Digital dalam Meningkatkan Pemikiran Kritis Siswa pada Mata Pelajaran Ekonomi - Nurul Fitria Hartanti; Muzakir Muzakir; Safka Mawarzani (Universitas Qamarul Huda Badaruddin, 2026)
This study aimed to examine the effectiveness of the Problem-Based Learning (PBL) model combined with a digital approach in enhancing students’ critical thinking skills in Economics at MA Qamarul Huda Bagu. Using a quantitative method with a quasi-experimental design, the research involved two classes: experimental and control. The critical thinking test instrument was validated and reliability-tested prior to use. Data were collected through pretests and posttests, then analyzed using paired t-tests and independent t-tests. The findings indicate a significant improvement in critical thinking skills among students in the experimental class compared to the control class. These results support constructivist theory, which emphasizes students’ active roles in problem-solving, and provide practical recommendations for teachers to integrate digital technology into classroom learning.